Model Kerjasama Pengelolaan Sampah Pada Tempat Pemrosesan Akhir Sampah (TPAS) Regional Sarimukti (Studi Kasus Kabupaten Bandung Dan Kota Bandung) - Teddy Permana; Abdullah; Deddy Mulyadi (LPPM UNSAP & FISIP UNSAP, 2022)
An issue related to waste and waste management is a problem that is getting more complicated from day to day and it is not immediately resolved in an integrated manner as the case for waste management in the Bandung Basin Urban Area, especially Bandung Municipality and Bandung Regency. As with the end of the age of land use at the Sarimukti Temporary Final Processing Site (TPAS), and there is still waste generation or residual residue that is not transported to the TPA per day ranging from 15% - 51.16% to piles of waste at the TPS, so that it can have an impact negative aspects ranging from public health problems, the reduced beauty of the city so that it becomes a threat, especially to the attractiveness of the region. Collaborative cooperation is needed in order to improve the quality of a clean and healthy environment. With the mechanism of waste management cooperation at the Sarimukti Regional TPAS, it can assist local governments in carrying out their duties in waste management. Looking at the current conditions regarding the existing cooperation in overcoming the constraints experienced by the local government of the Bandung Basin Urban Area in waste management, it is necessary to have a model of cooperation between local governments and stakeholders in waste management as a solution in improving the quality of a clean and healthy environment, through a cooperative model. based on the theory of collaborative governance (Ansel and Gash, 2007) so as to create integration and collaboration of waste management processes from and or between upstream to downstream, at the Sarimukti Regional TPAS. So that the implementation of waste management cooperation at the Sarimukti Regional Final Waste Processing Site (TPAS), as well as the recommendations of researchers including: a policy brief can be drawn up as a supporting document for policies on handling waste management in the Regency / City area which is carried out through waste management cooperation, or creating technological innovations which can provide solutions to problems in waste management at the Sarimukti Regional TPAS